Ukraine : Ex Post Evaluation of Exceptional Access Under the 2014 Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Ukraine's Ex Post Evaluation of Exceptional Access Under the 2014 Stand-By Arrangement (SBA) program. The SBA program faced substantial geopolitical risks from the outset, but rightly focused on immediate and medium-term objectives. Important steps were taken under the program. The authorities made effective strides early on, including in longstanding difficult areas, such as raising energy tariffs and largely maintaining a flexible exchange rate, albeit with occasional sizeable interventions. Banking sector diagnostics were conducted for the largest banks and a large number of them were resolved in an orderly manner. Naftogaz restructuring also began under the SBA, as did anticorruption and governance reform.